Servitization intent as a factor in the servitization process. Issue 8 (1st October 2018) - Crowley, Edward; Burton, Jamie; Zolkiewski, Judith
Abstract : Purpose: This paper aims to investigate the role of servitization intent in the servitization process, and specifically the role dissonance (at an organizational level) in servitization intent can play in creating barriers to the servitization effort. Servitization intent is defined as the desire to achieve a future state of increased servitization. Design/methodology/approach: The research uses elite interviews and secondary data to explore servitization intent and its role during the servitization process. It examines the resistance to change resulting from a misalignment of the executive intent to servitize, and the organizational intent to retain the existing manufacturing business model. By encompassing data from companies representing a significant portion of the total industry (as measured by revenue), the study provides an industry level perspective of servitization intent and alignment. Findings: Servitization intent and three key managerial challenges related to servitization intent that act as barriers to servitization were identified: lack of servitization intent, overcoming the manufacturing mindset associated with the organizational intent and the constraints resulting from managerial experience. Servitization intent and its associated managerial challenges were present at an industry level with consistent findings being shown across the major firms in the industry studied. A number of managerial strategies for overcoming these barriers were identified. Research limitations/implications: The research focuses on a single industry; the findings, potentially, have application across a broad range of industries. Practical implications: A key management implication from these findings is the need for a clear understanding of the organizational intent in relation to servitization in addition to the need to bring this organizational intent in alignment with the executives' servitization intent. Originality/value: This research makes a contribution by identifying the misalignment between servitization intent in different levels of the organization during the servitization process and the mechanisms that can improve alignment and help effect servitization.